1975
DOI: 10.1002/cjce.5450530112
|View full text |Cite
|
Sign up to set email alerts
|

SO2 promoted oxidative dehydrogenation of ethylbenzene

Abstract: It has been demonstrated that SO2 acts as an efficient dehydrogenation agent in the conversion of ethylbenzene to styrene in the presence of alkali and alkaline earth metal oxide doped alumina and titania catalysts. Development of these catalysts, which give styrene yields of greater than 80% per pass, is described in the paper. The catalysts allow the use of close to stoichiometric amounts of sulphur dioxide, are active in the presence of steam diluent and show low deactivation with time. The effect of varyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…15 Some studies have also been performed on the effect of H 2 S or other sulfur species on the ODH reactions of light alkanes. 13,14 Initial works by Tischler and Wing 17 and Porchey and Royer 18 have demonstrated the merits of adding H 2 S to an uncatalyzed system for the dehydrogenation of propane. The promoting properties of H 2 S were further explored by Clark et al, 19 and they observed that the conversion and propylene selectivity of the propane ODH reaction over V 2 O 5 /Al 2 O 3 were enhanced to 53.7 and 56.5%, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Some studies have also been performed on the effect of H 2 S or other sulfur species on the ODH reactions of light alkanes. 13,14 Initial works by Tischler and Wing 17 and Porchey and Royer 18 have demonstrated the merits of adding H 2 S to an uncatalyzed system for the dehydrogenation of propane. The promoting properties of H 2 S were further explored by Clark et al, 19 and they observed that the conversion and propylene selectivity of the propane ODH reaction over V 2 O 5 /Al 2 O 3 were enhanced to 53.7 and 56.5%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Another approach of reducing the overoxdiation of alkane and olefins in the ODH reactions is the use of an additive or a milder oxidant. Species such as halogens, sulfur-containing compounds, N 2 O, and CO 2 have been tested respectively. CO 2 with ceria-based catalyst increased the ethylene selectivity in the ethane ODH reaction to about 60% but a much higher reaction temperature was required because of the low activity of CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The former approach involving mostly membrane reactors has limited applicability due to their sensitivity towards certain species present in the reaction and also a cost factor. The other approach involves the introduction of oxidant molecules such as oxygen, halogens, sulfur and more recently mild oxidant like CO 2 in the dehydrogenation of ethylbenzene to overcome thermodynamic constraints [6][7][8]. However, development of commercial process was not successful to manufacture styrene by oxidative DHEB because of loss of styrene selectivity in addition to safety factors.…”
Section: Introductionmentioning
confidence: 99%